A program of physical activity improves gait impairment in people with Alzheimer's disease - Orcioli-Silva, Diego [UNESP]; Barbieri, Fabio Augusto [UNESP]; Simieli, Lucas [UNESP]; Dos Santos, Paulo Cezar Rocha [UNESP]; Beretta, Victor Spiandor [UNESP]; De Melo Coelho, Flávia Gomes; De Andrade, Larissa Pires; Gobbi, Lilian Teresa Bucken [UNESP] (FapUNIFESP (SciELO), 2018)
Aim: This study aimed to identify the effects of aging and Alzheimer's disease (AD) on gait parameters after a four-month period and to investigate the effects of a four-month program of physical activity, with emphasis on the cognitive components of gait during single and dual task, in people with AD. Methods: Twenty-three people with AD, divided into the Training Group (TG; n=12; aged 79.17±7.62 years) and the Control Group (CG; n=11; aged 77.00±5.57 years), and eleven healthy older adults (Healthy Group - HG; aged 75.82±4.83 years) were included in this study. TG participated in a physical activity program for four months. The CG and HG were instructed not to participate in any kind of regular physical activity in this period. The physical activity program includes motor activities and cognitive tasks simultaneously. The participants attended a 1-h session three times a week. The kinematic parameters of gait were analyzed under two conditions, before and after a physical activity program: Single and dual task. Deltas for all dependent variables between pre and post training were calculated. The deltas were compared using two-way ANOVAs with group (TG x CG and CG x HG) and task (single x dual task) as factors, with repeated measures for task. Results: After the training period, the TG improved stride length, duration, velocity and cadence compared to the CG. Conclusion: Physical activity with emphasis on cognitive components promotes better reallocation of attention while walking in people with AD, improving attentional focus on the gait and thus resulting in a safer locomotive pattern.
Keywords: Alzheimer's disease; Cognitive components; Dual task; Gait impairments; Physical activity